Renewable and resilient power systems under future climate variability - Figueiredo, Raquel Vaz Pato (2020)
The concern about the consequences of carbon-intensive activities across all socio-economic sectors is accelerating the path towards renewables-based power systems. However, larger renewable energy penetration allied with unknown future demand adds vulnerability and uncertainty to the design of power systems. This work assesses the impact of climate variability and energy demand in renewables-based power systems. An hourly-based modelling tool is used to simulate the power system for Portugal in 2050. A multiyear model calibration is proposed, enabling a more reliable simulation. Regarding climate, two representative concentration pathways (RCP4.5 and RCP8.5), totaling 473 climate realizations, are tested. Five electricity demand-flexibility scenarios are tested for each activity sector, assuming diverging levels for electricity demand, storage and demand-side management. The impacts of climate variability on supply and demand are simultaneously analyzed and quantified. Energy demand plays a crucial role in the power system. Results show that residential demand may increase between 4 and 60%, which are used to define scenarios. The cross-border interconnection needs quadruplicate from low to high demand, while the renewable generation share decreases 16 p.p. Climate variability, depending on the scenario, leads to changes in residential demand between -8 to +5% around its median, while renewables generation share might oscillate between -15 and +15 p.p. Cross-border interconnection energy trading needs may vary by a factor of two due to climate variability, from -62 to +226% around its median. Fully renewables-based power systems are especially vulnerable to climate. The system power capacity required under a climatic median year varies 3-fold according to demand-flexibility scenarios. For that same system to be resilient under unfavorable years, it is required an increase of up to 200-fold in storage or doubling of cross-border interconnection. A power system designed for unfavorable years requires 54% more installed capacity. Hence, future climate variability will be critical in the power systems’ operation, thus pivotal to evaluate and consider in its planning.